See the unseen: applications of imaging techniques to study adsorption in microporous materials. (June 2019) - Pini, Ronny; Joss, Lisa
Abstract : Chemical processes that incorporate porous solids (adsorbents and catalysts) include transient and spatially localised phenomena. Their thorough understanding requires the development of experimental methods that enable in situ observations made under process conditions. Imaging techniques are providing an unprecedented level of detail in the study of adsorption, both in the gas and liquid phase, including spatiotemporal measurements of adsorption equilibrium, kinetics and dynamics in microporous solids. The available techniques range from microscopy to multidimensional spectroscopy and tomography, and enable the development of so-called digital workflows, where adsorbent properties can be computed from spatially distributed adsorption uptake curves and isotherms. The widespread applicability of these methods is expected to pave the way towards resolving the complex structure of adsorption systems, from nano-scale to macro-scale, while providing new fundamental understanding of adsorption processes operando.